Factors influencing academics' research engagement and productivity : A developing countries perspective - Heng, Kimkong; Hamid, M. Obaidul; Khan, Asaduzzaman (Issues in educational research, 2020)
Academics are under increasing pressure to publish, particularly in peer-reviewed journals. This external pressure is clearly expressed by the 'publish or perish' dictum. Studies have shown that academics' engagement in research and their research productivity are influenced by personal as well as environmental factors. Based on an extensive review of literature, this paper demonstrates that the various factors affecting research engagement and productivity of academics can be classified into three different levels: individual, institutional, and national. All these factors can be schematically summarised into an analytical or conceptual framework to study research engagement and productivity, particularly in developing countries. Pointing to the 'North-South' gap in knowledge production and its implications for building knowledge economies, the paper concludes with directions for further research. [Author abstract]